Developing a Green Governance Framework for the Performance Enhancement of the Oil and Gas Industry - Shah, S.Q.A. (MDPI, 2022)
Green governance is an emerging concept that has received considerable attention from academics and industry over the last decade. Nevertheless, limited evidence is available on how green governance can affect the overall performance of firms. Accordingly, the study develops a green governance framework and establishes its relationship with the firm performance measured through shareholder value-added. While developing a new framework, this study integrated enterprise risk management, sustainability indicators, and green board committees to provide a holistic view of green governance. A contentious examination of the extant literature indicates the efficacy of these factors in mitigating economic, social, environmental, and governance risks. Firms, coping with these risks through the execution of a green governance framework, ensure shareholdersâ interest by enhancing their financial returns and stakeholders through promoting sustainability. The study provides theoretical and practical insights to the policymakers, regulators, and practitioners of the oil and gas industry in promoting sustainable and cleaner operations by executing a green governance framework. To the best of the authorsâ knowledge, this is the first study to propose an integrated green governance framework for the performance enhancement of oil and gas companies. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.